Excessive daytime sleepiness in nursing technicians: association with sleep quality and memory - Renato Canevari Dutra da Silva; Ana Clara Barros Ribeiro; Maryanna Freitas Alves; Gilson Gonçalves Silva; Elton Brás Camargo Júnior (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to investigate excessive daytime sleepiness prevalence among nursing technicians and the association with sleep quality and memory. Methods: a cross-sectional, inferential study, carried out in a hospital unit in the state of Goiás between December 2020 and January 2021. Assessments were carried out using the Epworth Sleepiness Scale, the Pittsburgh Sleep Quality Index and the Prospective and Retrospective Memory Questionnaire, instruments validated for the Brazilian context. Bivariate and multivariate logistic regression analyzes were performed. Results: the sample consisted of 189 nursing technicians with a 40.9% excessive daytime sleepiness prevalence. In multivariate models, excessive daytime sleepiness was not associated with sleep quality, however there was a significant association with overall memory failures. Conclusions: study results demonstrate a high excessive daytime sleepiness occurrence, an association with overall memory failures and the need for psychosocial interventions for nursing technicians.